Analysis of suppliers’ resilience factors under uncertainty - KILIÇ, HÜSEYİN SELÇUK; TUZKAYA, GÜLFEM (My University, 2023)
Selecting a resilient supplier is an essential component in supply chain management. Resilient suppliers can tolerate supply chain disruptions brought on by unforeseen events like natural catastrophes, economic downturns, and other unforeseen occurrences. Organizations may reduce the risks of supply chain disruptions and enhance the overall stability and sustainability of their supply chains by selecting resilient suppliers. To select a resilient supplier, organizations should take into account a variety of aspects, such as the supplier\"s financial stability, risk management capabilities, degree of operational and supply chain redundancy, and dedication to ongoing development. In this study, it is aimed to reveal and assess the resilience factors in the selection of suppliers. Accordingly, the literature is searched and the most frequently examined resilience factors in the literature are determined via Pareto analysis. Afterward, Pythagorean Fuzzy DEMATEL method is used to evaluate the determined resilience factors. As a result, from the most important to the least, the resilience factors are found to be agility flexibility, responsiveness, visibility, robustness, redundancy, surplus inventory, and cooperation.
Keywords: Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; TELEKOMÜNİKASYON; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; TELECOMMUNICATIONS; ENGINEERING, ELECTRICAL & ELECTRONIC; Fizik Bilimleri; Bilgisayar Ağları ve İletişim; Control and Systems Engineering; Physical Sciences; Computer Networks and Communications; Pareto Analysis; Pythagorean Fuzzy DEMATEL; Resilience Factors; Resilient Supplier; Supplier Selection